Evaluation of agrobiodiversity and its trophic interactions as an indicator of sustainability in productive systems - Taraborelli P; Carrasco N; Malaspina M; Domínguez MC; Belaus A; López A; Scavone AS; Barbera A; Zamora MY (Open Journal of Environmental Biology - Peertechz Publications, 2022)
Agriculture has intervened, modified, and simplified ecosystems to obtain some goods and services. Conventional o industrial agriculture emphasizes the use of external inputs and the homogeneity of the landscape; agroecology promotes biodiversity to maximize biological interactions and their ecosystem services. The objective was to evaluate agrobiodiversity and its trophic interactions as an indicator of sustainability by comparing: industrial productive systems, and agro-ecological and semi-natural sites in the southern Pampas region. Samples were taken of mammals, birds, arthropods, and vegetation; with different indices, the food chains and the state of the system were evaluated. The results show that agricultural intensification simplifies landscape structure with a loss of biodiversity and the absence of functional groups (herbivores and nectarivorous). In agroecological wheat, the highest density of links was found and in agroecological pastures the highest grouping coefficient, this reveals greater cohesion and integration among the components of the system and more mechanisms of self-regulation. The agroecological diversity Index showed no differences between the management, this could be related to the presence of a biological corridor in the conventional field that would be increasing biodiversity. The key to achieving sustainable agroecosystems is to procure biodiverse landscapes with patches and corridors of shrub and herbaceous species.